The effect of deforestation in equatorial Africa on rainfall in central Sudan (MAUSAM, 1987)
Forests in most parts of the world were not taken seriously as to effect total amounts of rainfall. In tropical Africa this may not be so. Africa, north of the equator, is the largest land mass in the tropics. Sensible heat source is abundant, potential evaporation is high, air mass is less humid and rain is of short duration.Data from central Sudan for the rainy seasons of 1953 and 1983 were compared for eight stations from April to October. The elements compared are: average temperature for the month and average monthly dew point observation at 1200 GMT monthly rainfall and prevailing wind direction.The study explains how a change in the forest density in equatorial Africa caused a change in the air mass characteristics. As a result the air reaching central Sudan has changed. The changes were mainly that the surface temperature of the air in central Sudan increased by a few degrees celsius and the dew point decreased in 1983 as compared to those monthly values of 1953.The southwesterlies monsoonal air weakened and so did the upper easterlies which are dominant during rainy season over central Sudan from 700 mb upward.